Medicinal Plants Their importance in Pharmaceutical Sciences - Kuntal Dasa; Kuntal Dasa (New Delhi Kalyani, 2013)
Medicinal plants have played a vital role in many ancient traditional systems of medication in world wide. Traditionally,people are believed on plant based medicine for their primary health care
Herbal drug Medicinal plant Aromatic plants
Keywords: Herbal drug, Medicinal plant, Aromatic plants